Evaluation of acute flaccid paralysis surveillance indicators in Sokoto state, Nigeria, 2012–2019: a secondary data analysis - Raji, Ismail Abdullateef (BMC Public Health, 2021)
BACKGROUND: Nigeria, the last endemic country in the WHO African Region, was certified free of Wild Polio Virus (WPV) in 2020. However, due to low immunity in some communities in Sokoto, outbreaks of the circulating Vaccine Derived Polio Virus (cVDPV) occur. The aim of this study is to evaluate the Acute Flaccid Paralysis (AFP) surveillance indicators in Sokoto state, Nigeria. METHODS: This retrospective study was an analysis of routinely collected AFP surveillance data between 2012 and 2019 by the Sokoto state surveillance network. We assessed the Sokoto state AFP surveillance system using the AFP surveillance performance indicators. We performed all analyses using Microsoft Excel 2019. RESULTS: Cumulatively, 3001 Acute Flaccid Paralysis (AFP) cases were reported over the evaluation period, out of which 1692 (56.4%) were males, and 2478 (82.4%) were below five years. More than half, 1773 (59.1%), had a fever at the beginning of the disease, and 1911 (63.7%) had asymmetric paralysis. The non-polio AFP rate (9.1 to 23.5% per 100,000 children < 15 years old) and stool adequacy rate (92.5 to 100%) indicate high sensitivity. The proportion of cases that had stool samples collected early, timely transported to the laboratory and arrived at the laboratory in optimal condition were all above the World Health Organization (WHO) minimum standard of 80%. There was inadequate profile documentation of some suspected cases. CONCLUSIONS: Sokoto State has exceeded the WHO minimum standards in most of the AFP surveillance indicators. The performance of the system is sufficient enough to detect any reintroduction of WPV into the state. However, there is a need for improvement in data quality.